Contextual Architecture pada Perancangan Pusat UMKM di Kabupaten Nunukan - Sardewi, Fauzia Armanda; AS, Zulkarnain; Ramadhani, Suci (TIMPALAJA : Architecture Student Journals, 2024)
Abstract Micro, small, and medium enterprises (MSMEs) play a crucial and strategic role in national economic development. Besides contributing to economic growth and job creation, MSMEs also distribute the results of development. This research aims to design an MSME Center in Nunukan Regency using a contextual architecture approach. The design methodology includes collecting primary data through field observations and secondary data through literature and precedent studies. Site selection considers factors such as land use, circulation, infrastructure, supporting facilities, and strategic location. From the three alternatives, the chosen location is on Ujang Dewa Street, Selisun, South Nunukan District, in accordance with the criteria and Regional Spatial Plan (RTRW). The design focuses on the skills and creativity of MSMEs in Nunukan Regency. This MSME Center is expected to become a hub for fulfilling daily needs and souvenirs for both local and wider communities, as well as stimulating economic revival. The central MSME design aims to enrich elements that reflect Nunukan's distinctive characteristics, aligning with the contextual architectural approach.